First documentation of population dynamics and reproductive biology of big-scale sand smelt, A. boyeri Risso, 1810 in the coastal waters of the Southeast Caspian Sea- Northern Iran - Hajiradkouchak, Eisa; Rahnama, Behzad; Fazli, Hasan (Frontiers in Marine Science, 2025)
IntroductionTo effectively manage fish stocks, evaluating various aspects of population dynamics is considered crucial. Understanding invasive species is essential for conservation efforts. This study represents the first documentation of population parameters.MethodsFor this purpose, the population dynamics parameters, including growth, mortality, and recruitment of A. boyeri, found in the Coastal Waters of the southeast Caspian Sea of Northern Iran, were analyzed using FiSAT II software. ResultThe analyzed specimens were sampled with a total weight range of 1.2 to 12.51 g and a total length range of 60 to 125 mm. The population has a 5-year life cycle. The length-weight relationship was estimated as W=0.0055 L3.0774 for males and W= 0.0083 L2.9185 for females. The slope value (b) of the length-weight relationships obtained for A. boyeri were between 2.69-3.13 with an average value of 2.91. While populations of A. boyeri showed negative allometric growth patterns, the males of exhibited positive allometric growth patterns, whereas the females had negative allometric growth patterns. The von Bertalanffy growth function fitted to back-calculated size at age data was: Lt = 126.5 [1- exp - 0.34(t + 0.234)] and Lt =131.3[1-exp- 0.35(t + 0.374)] for males and females respectively. The average relative condition factor was reported to be 0.62 and 0.79 for males and females respectively. The growth performance index (∅’) was reported to be 1.74 and 2.10 for males and females respectively. The total mortality of 1.73 year–1, consisting of natural mortality of 1.38 year–1 and fishing mortality of 0.35 year–1 and 1.21 year–1, consisting of natural mortality of 0.90 year–1 and fishing mortality of 0.31 year–1 was reported for males and females respectively. An exploitation rate of 0.20 and 0.26 for males and females respectively, is suggestive of a less exploited state of the fish. For both sexes, the length at first maturity was found to be higher than the length at first capture, a condition that can disturb the stock, as such the utility of a net with a relatively larger mesh size is advisable. The sex ratio was 1:1.34 in favor of females. For both sexes, the reproductive season, evaluated from GSI, extended from March to June, with a peak in April. The average absolute and relative fecundities were 2865 eggs and 684 eggs g-1 of body weight respectively. The diameter of oocytes ranged from 0.028 to 0.25 mm with a mean value of 0.54. DiscussionThe life-history patterns of A. boyeri in the population under study imply that the population of this species in the southeast Caspian Sea differs markedly from those of other localities of its range distribution. The differences were thought to be due to differences in geographical locations. The current research on the population dynamics of A. boyeri can be used as the baseline data for its management stocks.